Infestation of entamoeba histolytica among the children of Mirpur cohort area, Dhaka - Rahman, Fatema; Khanum, Hamida; Uddin, Md Hafiz; Haque, Rashidul (Dhaka University Journal of Biological Sciences, 2011)
Entamoeba histolytica is one of the deadly species of protozoan parasites and is associated with pathological abnormalecies in liver and large bowel in human body. To detect the prevalence of E. histolytica, 350 stool samples were examined by a number of diagnostic techniques. Routine microscopic examination detected 27.3% prevalence of E. histolytica in symptomatic stool samples and 8.6% in asymptomatic stool samples. Dipstick test detected the same prevalence (27.3%) like that of microscopy in case of symptomatic stool samples, but 10.32% was in asymptomatic samples. ELISA detected 9.09% prevalence in symptomatic samples and 3.5% in asymptomatic samples. The females were found more infected than males and the most infective group detected by different techniques was 9-10 years children. Key words: Infestation; Entamoeba histolytica; Stool; Dipstick; ELISA DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8943 DUJBS 2010; 19(1): 47-52